TINJAUAN KONSEP DISIPLIN DALAM PENDIDIKAN ISLAM TERHADAP PROKRASTINASI AKADEMIK MAHASISWA FAKULTAS AGAMA ISLAM UNISA PALU - Ahmad, Ahmad; Nenny Kurniaty; Minan Nur; Kahar, M. Iksan (Musawa: Journal for Gender Studies, 2025)
Academic procrastination is one of the problems faced by many students, including at the Faculty of Islamic Religion, UNISA Palu. This behavior of delaying tasks has an impact on low academic achievement and delays in completing studies. This study aims to analyze the relationship between the concept of discipline in Islamic education and students' academic procrastination level. The study used a quantitative approach with a simple linear regression method. Prior to regression analysis, validity, reliability, and normality tests were conducted to ensure data quality. The research sample amounted to 141 students who were randomly selected. The results showed that 96% of students still experienced academic procrastination, while 4% had a fairly high level of discipline. Simple linear regression analysis showed a significant negative relationship between the level of discipline in Islamic education and academic procrastination behavior. The higher the level of discipline of students, the lower their tendency to procrastinate. This is in line with the concept of discipline in Islamic education which emphasizes the importance of time management, responsibility, and commitment to scientific mandates. The findings provide important implications for educational institutions, especially in designing strategies to improve student discipline through an Islamic values-based approach. The results of this study are expected to be a reference in the